Focus on form: A critical review. (May 2016) - Ellis, Rod
'Focus on form' (FonF) is a central construct in task-based language teaching. The term was first introduced by Michael Long to refer to an approach where learners' attention is attracted to linguistic forms as they engage in the performance of tasks. It contrasts with a structure-based approach – 'focus on forms' (FonFs) – where specific linguistic forms are taught directly and explicitly. However, there is perhaps no construct in second language acquisition (SLA) that has proved so malleable and shifted in meaning so much. This review article begins by considering how Long's original definition of it has stretched over time and then offers an updated definition of the construct based on the view that the term is best used to refer to specific kinds of 'activities' or 'procedures' rather than to an 'approach'. A classification of different types of focus-on-form activities/procedures is then presented. There follows a discussion of focus on form from a psycholinguistic and discoursal perspective along with a review of research relevant to these perspectives. The article addresses a number of criticisms that have been levelled against focus on form, with special consideration paid to how focus on form can be utilized in instructional contexts where more traditional (i.e. FonFs) approaches have been the norm.